Factors contributing to the proficiency levels of TESL students / Sheikha Majid - Majid, Sheikha (2014)
The proficiency levels of English teachers in Malaysia recently have been given much attention by the Ministry of Education. Due to this issue, this study focused on the proficiency levels of Malaysia’s potential English teachers. The objectives of this study are to determine the proficiency levels and identify the factors that contribute to the proficiency levels of TESL students. The Certificate of Proficiency in English (CPE) test was administered to 50 TESL students to find out their proficiency levels. The 5 most proficient respondents and the 5 least proficient respondents were interviewed in order to discover the factors that contribute to the respondents high and low proficiency levels. The results of the CPE show that only 1 respondent is ranked in the very strong performance level, 19 respondents are ranked in the borderline pass level, 26 respondents are ranked in the weak level and 3 respondents are ranked in the fail level. The interviews revealed 6 main factors that contribute to the high and low levels of proficiency. These factors are 1) Communication in English at home, 2) Communication in English in school or during English lesson, 3) Encouragement from English teachers, 4) Effort to improve English language proficiency, 5) Lack of encouragement from the environment to communicate in English, and 6) Negative attitude towards the English language. This study gives awareness concerning the proficiency levels of TESL students and the factors contributing to the proficiency levels as these aspects are important and have a strong impact on the quality of teaching English. Further studies should be done as there could be more undiscovered factors that could add to the factors found in this study.